The market potential of Isuzu Rodeo pickup in Malaysian automotive industry / Salmi Mohd Isa - Mohd Isa, Salmi (2000)
This research describes as a market survey to the crew cab 4x4 pickup Rodeo for ACM. So far ACM does not have a market survey on this latest TF series. Research is based on information that is available within ACM or that can be found through research. The economic down turn forces ACM to focus on every single sale because each sale counts in these days. To obtain these sales, marketing has to put a great effort in achieving its goal and objectives. This research gives an overview of what marketing department is actually doing and what is the market potential for Rodeo pickup so far Hopefully, the research findings shall help the department to identify their strengths, weaknesses, opportunities and threats (SWOT) in the current market. At the end the research gives recommendations and suggestions towards the improvements of Rodeo marketing strategies and action plans.